Non Goverment Organisation (NGO): Role NGOs Film in Malaysia for Literature - Kechot, Ab Samad; Daeng Jamal, Daeng Haliza (Journal of Techno-Social, 2011)
This writing aims to discuss the progression of several Malaysia’s film of non-governmental organizations (NGOs). It seeks to explore the history of NGOs film’s from the golden age of ‘Jalan Ampas’ to date as well as to examine the roles of these organizations played in the film industry. This paper also a part of a Master’s research entitled the role of Film’s Non-Governmental Organizations (NGOs) Leader: study of the several NGOs. Research methods used are library research and field studies. Library research has been made for secondary data while field studies run for interview, questionnaires for NGOs members and data from NGOs reports. The data was analysed using Statistical Package for the Social Science (SPSS), as for interview was conducted among the leaders of selective NGOs and also on the opinion leader who are a film activists. However, this study is limited to a few selected NGOs film only. Findings of this study found that the Association of Film Artists of Malaya (PERSAMA) is the pioneer for NGOs film’s and a basic struggle for workers move in the film based on volunteerism. At present, the observed association is actively championing the aspirations of five associations that are under the Combined Staff Association of Film Malaysia (GAFIM), Malaysian Association of Artists (SENIMAN), Malaysian Film Producers Association (PFM), Film Director Association of Malaysia (FDAM), and Screen Writers Guild of Malaysia (SWAM) and Film Employees Association of Malaysia (PROFIMA).The findings of this study found that many efforts have been made to enhance the film’s quality and place more films to international level.